"Experience Isn't Everything": How Emotion Affects the Relationship Between Experience and Cue Utilization. (August 2018) - Crane, Monique Frances; Brouwers, Sue; Wiggins, Mark William; Loveday, Thomas; Forrest, Kirsty; Tan, Suyin Giselle Marianne; Cyna, Allan Michael
Objective: This research examined whether negative and positive arousal emotions modify the relationship between experience level and cue utilization among anesthetists. Background: The capacity of a practitioner to form precise associations between clusters of features (e.g., symptoms) and events (e.g., diagnosis) and then act on them is known as cue utilization . A common assumption is that practice experience allows opportunities for cue acquisition and cue utilization. However, this relationship is often not borne out in research findings. This study investigates the role of emotional state in this relationship. Method: An online tool (EXPERTise 2.0) was used to assess practitioner cue utilization for tasks relevant to anesthesia. The experience of positive and negative arousal emotions in the previous three days was measured, and emotion clusters were generated. Experience was measured as the composite of practice years and hours of practice experience. The moderating role of emotion on the relationship between experience and cue utilization was examined. Results: Data on 125 anesthetists (36% female) were included in the analysis. The predicted interaction between arousal emotions and the experience level emerged. In particular, post hoc analyses revealed that anxiety-related emotions facilitated the likelihood of high cue utilization in less experienced practitioners. Conclusion: The findings suggest a role for emotions in cue use and suggest a functional role for normal range anxiety emotions in a simulated work-relevant task. Application: This research illustrates the importance of understanding the potentially functional effects common negative arousal emotions may have on clinical performance, particularly for those with less experience.